Keefektifan E-Modul Pembuatan Blok V terhadap Hasil Belajar Teknik Pemesinan Frais: Studi Eksperimen pada Siswa Kelas XI Teknik Pemesinan SMK - Fahrul Kurniawan; Shohihatur Rohman (Universitas Pendidikan Ganesha, 2026)
This study aims to test the effectiveness of using E-Modules on V-block manufacturing competencies towards the cognitive learning outcomes of 11th-grade Mechanical Engineering students. We used a quasi-experimental method with a nonequivalent control group design. The sample included 34 students purposively selected based on material completion criteria. Data was collected through multiple-choice tests given before and after the treatment in the experimental class. The collected data was analyzed using descriptive statistics and the Wilcoxon test since it wasn't normally distributed. The results showed a significant increase in the class's average score, going from 69.15 in the pretest to 89.91 in the posttest. Hypothesis testing also confirmed a statistically significant difference in concept understanding. The normalized gain score analysis put the effectiveness of this media in the medium category. The study concludes that using E-Modules is moderately effective in helping students independently master concepts and work procedures, making it a good alternative solution to overcome the lack of practical facilities in vocational high schools.